2019
DOI: 10.2147/cmar.s232421
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Noncoding RNA GAS5 Acts As A Tumor Suppressor In Laryngeal Squamous Cell Carcinoma Via miR-21 [Corrigendum]</p>

Abstract: Cancer Management and Research is an international, peer-reviewed open access journal focusing on cancer research and the optimal use of preventative and integrated treatment interventions to achieve improved outcomes, enhanced survival and quality of life for the cancer patient. The manuscript management system is completely online and includes a very quick and fair peer-review system, which is all easy to use. Visit http://www.dovepress.com/testimonials.php to read real quotes from published authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…More and more studies have proved that lncRNAs play a crucial role in the multi‐steps of tumour development 17 . For instance, lncRNA growth arrest‐specific 5 (GAS5) suppresses LSCC progression through the negative regulation of miR‐21 and its targets involved in cell proliferation and apoptosis 18 . Our previous research has demonstrated that lncRNA nuclear paraspeckle assembly transcript 1 (NEAT1) regulates CDK6 expression mediated by miR‐107 in LSCC, which may be a potential target for therapeutic intervention of LSCC 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more studies have proved that lncRNAs play a crucial role in the multi‐steps of tumour development 17 . For instance, lncRNA growth arrest‐specific 5 (GAS5) suppresses LSCC progression through the negative regulation of miR‐21 and its targets involved in cell proliferation and apoptosis 18 . Our previous research has demonstrated that lncRNA nuclear paraspeckle assembly transcript 1 (NEAT1) regulates CDK6 expression mediated by miR‐107 in LSCC, which may be a potential target for therapeutic intervention of LSCC 19 .…”
Section: Introductionmentioning
confidence: 99%
“…17 For instance, lncRNA growth arrest-specific 5 (GAS5) suppresses LSCC progression through the negative regulation of miR-21 and its targets involved in cell proliferation and apoptosis. 18 Our previous research has demonstrated that lncRNA nuclear paraspeckle assembly transcript 1 (NEAT1) regulates CDK6 expression mediated by miR-107 in LSCC, which may be a potential target for therapeutic intervention of LSCC. 19 It has been proved that m6A-methylated level can affect the expression of lncRNA, and regulate the development of tumour.…”
mentioning
confidence: 99%
“…13 Furthermore, Lyu et al showed that lncRNA GAS5 inhibited cell proliferation and increased the cell apoptosis rate in laryngeal squamous cell carcinoma by regulating the miR-21/BAX/CDK6 axis. 14 However, Lyu’s study had some limitations. 14 First, the function and relative regulatory mechanism of lncRNA GAS5 on laryngeal cancer cell migration and invasion ability in vitro have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…14 However, Lyu’s study had some limitations. 14 First, the function and relative regulatory mechanism of lncRNA GAS5 on laryngeal cancer cell migration and invasion ability in vitro have not been elucidated. Second, in vivo animal experiments have not yet been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, long intergenic non-protein coding RNA 987 mitigates COPD by regulating lipopolysaccharide (LPS)-caused cell apoptosis, oxidative stress, inflammation and autophagy via the Let-7b-5p/sirtuin1 axis ( 30 ). Growth arrest-specific 5 (GAS5), a well-documented lncRNA, is an important factor associated with cell proliferation and death in various diseases ( 31 , 32 ). GAS5 acts as a ceRNA to sponge miR-223-3p in certain diseases.…”
Section: Introductionmentioning
confidence: 99%